A Review of The Challenges of Paperless Concept In The Society 5.0 - Prasetyo, S.E.; Damaraji, G.M.; Kusumawardani, S.S. (Universitas Atma Jaya Yogyakarta, 2020)
The world will start a new era of society where technology and humans can collaborate to solve social problems. Many countries have ridden into the 4.0 era in the industrial revolution. In reality, Japan began to introduce Society 5.0, where the concept was the answer to the industrial revolution 4.0. Society 5.0 applies the human-centered concept based on information technology. In fact, there has been no in-depth study of the advantages and challenges of implementing paperless in various fields. The purpose of this paper is to review the challenges and the advantages of the paperless concept using Narrative Literature Review to provide an objective analysis of the paperless concept. The objects research discussed including industry/manufacturing, education, medical, and government. This paper provides an in-depth study and analysis of the paperless concept's advantages and challenges related to hardware and software maintenance, data security and reliability, human resources technical skills, social interaction, and disaster recovery strategy.